PENINGKATAN SUMBERDAYA PETANI MELALUI PENYULUHAN DAN PELATIHAN PEMBUATAN PUPUK ORGANIK - Mira Herawati Soekamto; Zainuddin Ohorella; Reijeng Tabara; Danang Supratman (Indonesian Collaboration Journal of Community Services, 2022)
The decline in soil quality in producing plants as a result of excessive fertilization, especially on inorganic fertilizers, has occurred on many lands in Indonesia. One of the things that happened was in Aimas Village, Sorong Regency, where farmers' land experienced a decrease in quality both in terms of chemical and physical properties. This happens because of the impact of the continuous use of chemical fertilizers over a long period of time which affects the decline in soil quality. Through extension activities and training on organic fertilizers, farmers can provide insight and skills on the benefits of organic fertilizers in improving soil properties, both physical, chemical and biological properties of the soil. The method used in this activity is a method or approach in transferring knowledge (counseling), practice of learning and doing (learning by doing/demonstration). From the results of this service activity, it was found that there was a change in farmers' knowledge of organic fertilizers which have an important role for land sustainability. The increase in knowledge changes to organic fertilizers is 80% and the adoption rate in the manufacture of organic fertilizers is 75%.